Music-Based Interventions for the Wellbeing of People in Prison: A Systematic Review - Roveda, Alex (Victims & offenders, 2025)
Music-based interventions are often used to improve the wellbeing of people in prisons. This systematic review evaluates the impacts of music-based interventions on wellbeing outcomes for both incarcerated adults and juveniles. Studies eligible for inclusion were limited to randomized control trials or strong quasi-experimental designs. Thirteen studies were deemed eligible and included in the review. Evaluated interventions included music-therapy, group music-making, choirs, and background music. Due to heterogeneity in interventions and outcomes, the effective direction of the interventions was plotted. Music-based interventions were generally linked to improved wellbeing outcomes across psychological/emotional, cognitive, and behavioral domains, however, effect sizes differed, and some studies showed negative effects. This review also highlights gaps in research for juveniles and women in prison and suggests future research should give closer attention to these populations.